Assessing dietary and lifestyle risk behaviours and their associations with disease comorbidities among patients with depression: A case-control study from Bahrain - Jahrami, Haitham (Heliyon, 2020)
OBJECTIVES: In Western populations, patients with depression die 10–25 years prematurely compared to controls, mainly due to lifestyle-related diseases. Tobacco smoking, excessive alcohol intake, poor diets and physical inactivity are among the major contributors to disease comorbidities. The objective of this research is to assess the dietary and lifestyle behaviours for Bahraini patients with depression and to determine their associations with different medical comorbidities. METHODS: A case-control study was conducted from March to December 2019. A sample of 96 diagnosed patients with depression was recruited from the Psychiatric Hospital/Bahrain, and 96 age- and sex-matched controls were recruited from primary health centres. Assessment of anthropometrics, dietary and alcohol intakes, tobacco smoking and physical activity levels were undertaken for both cases and controls. National electronic medical records were reviewed retrospectively for medical comorbidities for the recruited cases. Logistic regression analysis was used to identify associations between lifestyle behaviours and medical comorbidities after controlling for confounding factors. RESULTS: Patients with depression reported higher intakes of energy and energy-yielding macronutrients (e.g., carbohydrates, protein, and fat); three-fold higher rates of tobacco smoking; and significantly lower levels of physical activity. Cases appeared to be at a doubled risk for developing obesity, diabetes type 2, hypertension, and musculoskeletal disorders. The risk for cardiovascular problems was similar for cases and controls. CONCLUSIONS: Poor dietary intakes, increased prevalence of smoking, and low levels of physical activity were evident in patients with depression in Bahrain; these factors were associated with some medical comorbidities.